Applying the Ngadhu Bhaga ethnomathematics method to foster mathematical reasoning in junior high school geometry - Wewe, Melkior; Bella, Maria Editha; Noge, Maria Desidaria (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study investigates the effectiveness of the Ngadhu Bhaga ethnomathematics approach in enhancing junior high school students’ mathematical reasoning in geometry. Method: A quasi-experimental design with a Non-Equivalent Control Group Pre-Test – Post-Test model was used. Participants included two groups of eighth-grade students taught with either the Ngadhu Bhaga approach or conventional methods. Data were collected through written tests and analyzed using an independent samples t-test. Findings: The analysis revealed that students who learned through the Ngadhu Bhaga ethnomathematics approach demonstrated significantly greater improvements in their mathematical reasoning compared to those taught using traditional methods. The approach enabled students to connect geometric concepts with culturally familiar contexts, fostering deeper understanding and reasoning skills. Significance: These findings affirm the value of integrating ethnomathematics into mathematics instruction. By making learning more meaningful and culturally responsive, the Ngadhu Bhaga approach promotes not only academic growth but also cultural appreciation, supporting inclusive and contextually relevant education.